2023
DOI: 10.3389/fendo.2022.1091107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bi-allelic KIF9 loss-of-function variants contributing to asthenospermia and male infertility in two Chinese families

Abstract: IntroductionAsthenozoospermia (AZS) is a leading cause of male infertility, affecting an estimated 18% of infertile patients. Kinesin proteins function as molecular motors capable of moving along microtubules. The highly conserved kinesin family member 9 (KIF9) localizes to the central microtubule pair in the flagella of Chlamydomonas cells. The loss of KIF9 expression in mice has been linked to AZS phenotypes.MethodsVariant screening was performed by whole exome sequencing from 92 Chinese infertile patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Its activity has been linked to mRNA transport 19 , macrophage podosome homeostasis 20 , and mitosis 21 . It has also appeared in screens related to breast cancer 22 , glioblastoma 23 , mouse inner ear development 24 , nuclear movement during skeletal muscle differentiation 25 , and sperm flagellum formation and maintenance 26,27 . However, Kif9’s fundamental cellular function remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Its activity has been linked to mRNA transport 19 , macrophage podosome homeostasis 20 , and mitosis 21 . It has also appeared in screens related to breast cancer 22 , glioblastoma 23 , mouse inner ear development 24 , nuclear movement during skeletal muscle differentiation 25 , and sperm flagellum formation and maintenance 26,27 . However, Kif9’s fundamental cellular function remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Kinesin-9A is an axonemal component protein localized along one of the central pair of microtubules (C2) [17][18][19] . The loss of kinesin-9A function causes defective ciliary motility in multiple species [20][21][22][23] . Structural studies have revealed that kinesin-9A adopts two states on the central microtubule, positioned 8 nm apart [17] , suggesting that kinesin-9A movement may regulate dynein-induced ciliary bending [17,18,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no observed movement of KIF9B within flagella, it is speculated that it is involved in PFR transport or the recognition of axoneme asymmetry for PFR assembly in Trypanosoma (Demonchy et al, 2009). In mammals, mutations in Kif9 have been linked to defective sperm motility and impaired fertility (Meng et al, 2022;Miyata et al, 2020). However, its function in motile cilia remains unexplored.A frameshift mutation of KIF6 has been found in a patient with intellectual disability and megalocephaly (Konjikusic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of whether Kif6, in other species, also contributes to ciliary trafficking of essential materials involved in cilia beating and recognition or establishment of axonemal polarity. In mammals, mutations in Kif9 have been associated with defective sperm motility and impaired fertility (Meng et al, 2022; Miyata et al, 2020). A frameshift mutation of KIF6 has been found in a patient with intellectual disability and megalocephaly (Buchan et al, 2014; Konjikusic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%